A diversidade fitofisionômica na Chapada do Araripe: uma análise fitogeográfica em Santana do Cariri/CE - Araújo, Jaine da Silva Nuvens Ferreira (2023)
Araripe Plateou is one of the exceptional spaces present in the Northeast of Brazil. In its vegetational context, it houses heterogeneous phytophysiognomies, such as: Savanna (Cerrado); Steppic Savanna (Carrasco) and Evergreen Seasonal Forest (Humid Forest) andVeredas. This master's research aimed to analyze the phytogeographic distribution in a stretch of slope of Araripe Plateou, in order to contribute to the understanding of the vegetationlandscape relationship in exceptional environments of Araripe Plateou. To this end, the objective was to carry out a study on the phytophysiognomic characteristics of Araripe Plateou, through a floristic and phytosociological survey, on a hillside section of the area located in Sítio Nicácio, municipality of Santana do Cariri–CE. To carry out the survey, the plot method was adopted, where 20 plots of 20 m × 20 m were made. A total of 1,618 individuals were recorded, of which 70 species were distributed in 39 families. The most representative families were Fabaceae with 16 species, Anacardiaceae with 4 species, Rubiaceae, Bignociaceae and Erythroxlacae with 3 species. The section analyzed presented a greater number of individuals from the arboreal component. The survey made it possible to analyze plant populations, finding great heterogeneity in relation to the heights of individuals and great diversity of species. From the analysis in relation to the dynamics of use and occupation, the different uses in space and time are perceived, and how anthropogenic activities are taking place in the area. In this context, the need to know, understand and plan how to manage and use the different areas based on their strengths and weaknesses was identified. With regard to exceptional environments, the importance of conserving these environments is evident, given the diverse contributions made to semi-arid environments and the populations that live in their surroundings.